Cathodic Protection Online Monitoring Using a Low Power Wide Area Network Communication System - Karyanto Herlambang; Irwan Setyo Wibowo; Maskuri Junaedi (Natural Sciences Engineering and Technology Journal, 2023)
Cathodic protection is a corrosion control and prevention system that is applied to underground pipe structures by providing an electric charge to the structure to be protected. An online monitoring system for cathodic protection is urgently needed to save costs and ensure operator safety in the field in the care of the protected structure. This study aimed to evaluate cathodic protection online monitoring using a low power wide area network (LPWAN) communication system. Cathodic protection online monitoring in this study was applied using LPWAN with a radio frequency of 433 MHz. In this work, the type of communication with wireless technology has been chosen with low power consumption and can accommodate the distance between test stations in the distribution pipeline. From the results of testing the cathodic protection online monitoring system, it can be seen that measurement data that has been done manually can be replaced in real-time and monitored remotely. This system is highly recommended for areas that have so far not been covered by manual measurements, for example, remote areas prone to flooding, swamps, and interference areas that require denser data information to make handling easier to do early.